Explaining the Male Native-Immigrant Employment Gap in Sweden: The Role of Human Capital and Migrant Categories - Marc-André Luik; Henrik Emilsson; Pieter Bevelander (Institute for the Study of Labor (IZA), 2016)
Despite having one of the most celebrated labor market integration policies, the native-immigrant employment gap in Sweden is one of the largest among the OECD countries. In this study, we use unique Swedish register data to try to explain the employment gap between male immigrants and natives. The results show that the traditional human capital theory only explains a small share of the immigrant-native gap. After controlling for human capital, demographic and contextual factors, large unexplained employment gaps still persists between immigrants and natives and between migrant categories. Our analysis indicates that admission category is an important determinant of employment integration, and that humanitarian and family migrants suffer from low transferability of their country specific human capital. The article highlights the need to consider migrant categories in integration research, and take into account international human capital transferability when explaining employment outcomes for immigrants.
Keywords: F22; J61; J68; 330; human capital; Sweden; labour market integration; migration categories; employment gaps